2003
DOI: 10.1046/j.1365-8711.2003.06505.x
|View full text |Cite
|
Sign up to set email alerts
|

The planetary nebula K 1-2 and its binary central star VW Pyx

Abstract: New data are presented of the post‐common‐envelope binary VW Pyx and its associated planetary nebula (PN), K 1‐2. The central star is found to be a single‐lined (and possibly double‐lined) spectroscopic binary and is a good candidate for a system in which the main‐sequence secondary star is more massive than the subdwarf primary star. The old PN has a high excitation level and a measured electron temperature, TO∼ 17 000 K for an assumed log ne= 2.7 cm−3. The so‐called ‘jets’ are found to be lower‐ionization re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 41 publications
7
45
2
1
Order By: Relevance
“…Kohoutek & Schnur (1982) determined the Zanstra (He ii) temperature of the star (79,000-91,000 K). Exter et al (2003b) reported that the central star of this post-CE binary is a single-lined or possibly a doublelined spectroscopic binary, where the primary star absorption lines can barely be resolved, while the emission line spectrum of the irradiated secondary dominates. The spectrum is very similar to that of V664 Cas (HFG 1).…”
Section: A22 K 1-2mentioning
confidence: 98%
“…Kohoutek & Schnur (1982) determined the Zanstra (He ii) temperature of the star (79,000-91,000 K). Exter et al (2003b) reported that the central star of this post-CE binary is a single-lined or possibly a doublelined spectroscopic binary, where the primary star absorption lines can barely be resolved, while the emission line spectrum of the irradiated secondary dominates. The spectrum is very similar to that of V664 Cas (HFG 1).…”
Section: A22 K 1-2mentioning
confidence: 98%
“…The central CCD was read out with 2 × 2 binning to give a 5.5 × 2.5 arcmin field-of-view sampled at 0.145 ′′ /pixel. Bond & Livio (1990), (d) Schwarz, Corradi & Melnick (1992), (e) Walsh & Walton (1996), (f) Heckathorn, Fesen & Gull (1982), (g) Pollacco & Bell (1997), (h) Hua, Dopita & Martinis (1998), (i) Corradi et al (1999), (j) Bond (2000), (k) De Marco (2009), (l) Corradi et al (2000), (m) Exter, Pollacco & Bell (2003), (n) Liebert et al (1995) Our primary focus in this work is on the new OGLE sample rather than previously well-studied known sample. Section 4 will present a selection of more detailed images of the OGLE sample than that provided in Fig.…”
Section: Narrow-band Optical Imagingmentioning
confidence: 98%
“…Perhaps the most ambiguous case being the highly collimated 'jet-like' pairs often quoted as 'jets' (e.g. Exter et al 2003) even though their velocities not substantially different from their nebulae (Gonçalves 2004). We describe knots as unresolved or small LIS with an aspect ratio of unity, and filaments as knots with an aspect ratio larger than unity (Gonçalves et al 2001).…”
Section: Low-ionisation Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest remaining candidate is, without doubt, PN SuWt 2 (Schuster & West 1976), a ring nebula (see figure 1) where the bright star closest to the projected nebular centre has been shown to be a 4.9 day period binary consisting of two, almost identical, A-type main-sequence stars (Bond et al 2002;Exter et al 2003). Exter et al (2010) performed a detailed analysis of this double A-type system (NSV 19992 from hereon; Kazarovets et al 1998), showing both components to be A1V stars of mass ∼2.7M ⊙ , neither of which could be the source of photoionisation nor the nebular progenitor (the nebular abundances indicate a post-AGB progenitor; Smith et al 2007).…”
Section: Introductionmentioning
confidence: 99%